Probiotics as a New Regulator for Bone Health: A Systematic Review and Meta-Analysis. (3rd August 2021) - Malmir, Hanieh; Ejtahed, Hanieh-Sadat; Soroush, Ahmad-Reza; Mortazavian, Amir Mohammad; Fahimfar, Noushin; Ostovar, Afshin; Esmaillzadeh, Ahmad; Larijani, Bagher; Hasani-Ranjbar, Shirin
Abstract : Despite the proposed role of the gut microbiota-bone axis, findings on the association between probiotic consumption and bone health are conflicting. This systematic review aimed to assess the effect of probiotic consumption on bone health parameters. A systematic literature search of relevant reports published in PubMed/Medline, Web of Science, SCOPUS, EMBASE, and Google scholar before December 2020 was conducted. All clinical trials or experimental studies, which examined the relationship between probiotic consumption and bone health parameters, were included. No limitation was applied during the search. After screening articles based on inclusion criteria, 44 studies remained. In clinical trials, probiotic consumption affects bone health parameters such as serum calcium levels (3.82; 95% CI: 1.05, 6.59 mmol/l), urinary calcium levels (4.85; 95% CI: 1.16, 8.53 mmol/l), and parathyroid hormone (PTH) levels (−5.53; 95% CI: −9.83, −0.86 ng/l). In most studies, Lactobacillus species such as L. helveticus, L. reuteri, and L. casei were consumed and women aged 50 years or older were assessed. Spinal and total hip bone mineral density (BMD) was not affected significantly by probiotic consumption. In 37 animal experiments, probiotic or symbiotic feeding mostly had effects on bone health parameters. Some strains of Bifidobacterium and Lactobacillus including L . reuteri, L. casei, L. paracasei, L. bulgaricus, and L. acidophilus have indicated beneficial effects on bone health parameters. In conclusion, this systematic review and meta-analysis indicate that probiotic supplementation might improve bone health. Further studies are needed to decide on the best probiotic species and appropriate dosages.